Proposals for the standards of patients referral in clinical oncology - Wiktor Jędrzejczak, Wiesław (Contemporary Oncology/Współczesna Onkologia, 2000)
Medicine functions as a system of complementary specialties and of hierarchical competence. Such system can offer optimal treatment to many patients providing that particular patient will receive treatment from the doctor in the center specifically prepared to provide such treatment and not necessarily from the doctor to whom he will contact first. Standards of referral in clinical oncology are designed to serve to delineate the clear principles of patients traffic to the parts of system the best prepared to serve their particular needs. For instance, they are designed to serve immediate referral of young patients with very aggressive cancers to specialized centers treating these cancers and also to allow old patients with slowly progressing neoplasia to receive service as close to their homes as possible. Additionally standards of referral are aimed in defining collaboration of doctors belonging to different specialties in combined modality cancer treatment.